Blended Learning Model in Elementary School : Systematic Literature Review - Muhamad Suhardi (Universitas Pendidikan Ganesha, 2025)
Blended learning model is an approach that combines face-to-face learning with online learning in an integrated manner, allowing for a more flexible and adaptive learning experience. This research aims to analyze learning management in the implementation of Blended Learning model in elementary school through Systematic Literature Review (SLR) approach. Data were collected from seven relevant scientific articles, obtained through a search on Google Scholar in March 2025 with a publication range of 2020-2024. The search began with the keyword